Older Lesbians' experiences of ageing in place in rural Tasmania, Australia: An exploratory qualitative investigation. (22nd May 2020) - Grant, Ruby; Walker, Briohny
Abstract: While there is increasing awareness of the specific health and aged care needs of older lesbian and gay people, little is known about their needs and experiences of ageing in rural communities. In Australia, older people are over‐represented in regional and rural areas, however, rural communities face particular challenges to age friendliness, including infrastructure and transport limitations, reduced health and social services. In this context, few studies explore older lesbians' gendered experiences of ageing in place. To address this gap in the literature, this article draws on qualitative interviews with 13 rural Tasmanian lesbians over the age of 55, exploring their perceived barriers and enablers for 'healthy ageing' in their communities. Findings reveal that geographical isolation was a literal barrier to accessing specialist healthcare and lesbian‐inclusive services, which may be absent in rural areas. The women perceived community health initiatives and social activities aimed at 'healthy ageing' in rural towns as heteronormative and unappealing for lesbians. In some cases women reported experiencing homophobic discrimination in these social groups. In contrast, rural communities were positively associated with a good quality of life derived from closeness to nature and feelings of reciprocity with rural neighbours and communities. These findings suggest that specific approaches to lesbian‐inclusive rural health and social care are required. Rural communities are well‐placed to build on community strengths to ensure higher quality of place‐based health and social care for isolated older people, including those of diverse genders and sexualities.